2009
DOI: 10.1091/mbc.e07-12-1248
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol Kinase ζ Regulates Actin Cytoskeleton Reorganization through Dissociation of Rac1 from RhoGDI

Abstract: Activation of Rac1 GTPase signaling is stimulated by phosphorylation and release of RhoGDI by the effector p21-activated kinase 1 (PAK1), but it is unclear what initiates this potential feed-forward mechanism for regulation of Rac activity. Phosphatidic acid (PA), which is produced from the lipid second messenger diacylglycerol (DAG) by the action of DAG kinases (DGKs), is known to activate PAK1. Here, we investigated whether PA produced by DGK initiates RhoGDI release and Rac1 activation. In DGK-deficient fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 72 publications
4
101
1
1
Order By: Relevance
“…During hepatocyte growth factor-mediated membrane ruffling in Madin-Darby canine kidney cells, diacylglycerol kinase (DGK)a promoted the translocation of atypical protein kinase Cz/i, stably associated with the RhoGDIa-Rac1 complex, to the PM through PA production (31). Additionally, it was reported that DGKz, stably associated with PAK1 and RhoGDIa-Rac1, promoted the release of RhoGDIa from Rac1 through DGKz→PA→PAK1-mediated RhoGDIa phosphorylation at platelet-derived growth factor-induced membrane ruffling in fibroblasts (32). These studies support an involvement of PA produced from DGK in regulation of RhoGDIa-Rac1 translocation to membranes and dissociation on membranes.…”
Section: Discussionsupporting
confidence: 53%
“…During hepatocyte growth factor-mediated membrane ruffling in Madin-Darby canine kidney cells, diacylglycerol kinase (DGK)a promoted the translocation of atypical protein kinase Cz/i, stably associated with the RhoGDIa-Rac1 complex, to the PM through PA production (31). Additionally, it was reported that DGKz, stably associated with PAK1 and RhoGDIa-Rac1, promoted the release of RhoGDIa from Rac1 through DGKz→PA→PAK1-mediated RhoGDIa phosphorylation at platelet-derived growth factor-induced membrane ruffling in fibroblasts (32). These studies support an involvement of PA produced from DGK in regulation of RhoGDIa-Rac1 translocation to membranes and dissociation on membranes.…”
Section: Discussionsupporting
confidence: 53%
“…EGFR activation is known to activate PLD and enhance phosphatidic acid levels in membrane microdomains (31). It is worth noting that both the F-BAR/FX of Fer and the poly-basic C domain of Rac1 bind to phosphatidic acid, leading to Fer activation and reduced Rac1 sequestration by RhoGDIa (11), (38), (39). Fer can also phosphorylate RhoGDIa directly to limit Rac1 binding (22).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, DGKζ was shown to regulate PAK1-mediated phosphorylation of RhoGDI, leading to selective activation of Rac but not of Cdc42 (30). Conversely, PKCζ-dependent phosphorylation of RhoGDI promotes the release of both Rac and Cdc42 (21).…”
Section: Discussionmentioning
confidence: 99%